Oxidative Stress and Microvessel Barrier Dysfunction - He, Pingnian; Talukder, M. A. Hassan; Gao, Feng (Frontiers in Physiology, 2020)
Clinical and experimental evidence indicate that increased vascular permeability contributes to many disease-associated vascular complications. Oxidative stress with increased production of reactive oxygen species (ROS) has been implicated in a wide variety of pathological conditions, including inflammation and many cardiovascular diseases. It is thus important to identify the role of ROS and their mechanistic significance in microvessel barrier dysfunction under pathological conditions. The role of specific ROS and their cross talk in pathological processes is complex. The mechanisms of ROS-induced increases in vascular permeability remain poorly understood. The sources of ROS in diseases have been extensively reviewed at enzyme levels. This review will instead focus on the underlying mechanisms of ROS release by leukocytes, the differentiate effects and signaling mechanisms of individual ROS on endothelial cells, pericytes and microvessel barrier function, as well as the interplay of reactive oxygen species, nitric oxide, and nitrogen species in ROS-mediated vascular barrier dysfunction. As a counter balance of excessive ROS, nuclear factor erythroid 2 related factor 2 (Nrf2), a redox-sensitive cell-protective transcription factor, will be highlighted as a potential therapeutic target for antioxidant defenses. The advantages and limitations of different experimental approaches used for the study of ROS-induced endothelial barrier function are also discussed. This article will outline the advances emerged mainly from in vivo and ex-vivo studies and attempt to consolidate some of the opposing views in the field, and hence provide a better understanding of ROS-mediated microvessel barrier dysfunction and benefit the development of therapeutic strategies.